Replacement of mouse Sox10 by the Drosophila ortholog Sox100B provides evidence for co-option of SoxE proteins into vertebrate-specific gene-regulatory networks through altered expression. - Sock, Elisabeth; Wegner, Michael; et al. (Developmental Biology, 2010)
Neural crest cells and oligodendrocytes as the myelinating glia of the central nervous system exist only in vertebrates. Their development is regulated by complex regulatory networks, of which the SoxE-type high-mobility-group domain transcription factors Sox8, Sox9 and Sox10 are essential components. Here we analyzed by in ovo electroporation in chicken and by gene replacement in the mouse whether the Drosophila ortholog Sox100B can functionally substitute for vertebrate SoxE proteins. Sox100B overexpression in the chicken neural tube led to the induction of neural crest cells as previously observed for vertebrate SoxE proteins. Furthermore, many aspects of neural crest and oligodendrocyte development were surprisingly normal in mice in which the Sox10 coding information was replaced by Sox100B arguing that Sox100B integrates well into the gene-regulatory networks that drive these processes. Our results therefore provide strong evidence for a model in which SoxE proteins were co-opted to these gene-regulatory networks mainly through the acquisition of novel expression patterns. However, later developmental defects in several neural crest derived lineages in mice homozygous for the Sox100B replacement allele indicate that some degree of functional specialization and adaptation of SoxE protein properties have taken place in addition to the co-option event. © 2010 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.replac
Keywords: Glia; High-mobility-group; Neural crest; Oligodendrocyte; Satellite glia; Schwann cell; Sry